Dexlansoprazole – a new-generation proton pump inhibitor - Skrzydło-Radomańska, Barbara; Radwan, Piotr (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Dexlansoprazole modified release (MR) is an R-enantiomer of lansoprazole and a new-generation proton pump inhibitor exhibiting high efficacy in the treatment of symptoms and lesions associated with erosive oesophagitis caused by gastroesophageal reflux disease (GERD). The dual release of the active ingredient – in the duodenum and the small intestine – makes it possible to achieve two peak concentrations at various times, within two and five hours of administration. Dexlansoprazole MR ensures the longest maintenance of drug concentration in the plasma of all known proton pump inhibitors, and the longest proton pump inhibitory effect. The basic indications for the drug include all forms of gastroesophageal reflux disease, especially with night-time heartburn and sleep disorders resulting from GERD. Dexlansoprazole can be taken regardless of meal times. It has a good safety profile and carries a low risk of adverse interactions with other drugs.